Risk Management in Sharia Financial Institutions (Case Study of BMT NU East Java Socah Bangkalan Branch) - Amalia Putri, Fauziah; Qadariyah, Lailatul (ILTIZAM Journal of Shariah Economics Research, 2023)
Risk is a state of uncertainty that may cause harm or loss to an Islamic financial institution that may occur as a result of ongoing or future processes. The risk will have an impact on Islamic financial institutions both operationally, financially and on the sustainability of an institution. Islamic financial institutions need to have risk management which is used as a systematic method used to identify, analyze, evaluate, manage, supervise and monitor emerging risks so as to minimize losses and maximize opportunities. The purpose of this study is to find out the types of risks that occur and to find out how to manage the risks carried out by BMT NU East Java Socah Bangkalan Branch. This research is descriptive in nature by using a qualitative approach through case studies and using the interview method and data collection from books, journals and the web. From the research conducted, it was found that the risks involved in BMT NU East Java Socah Bangkalan Branch are operational risk, reputation risk, fraud risk, financing risk and business risk. Settlements made, namely visits to customers and the obstacles encountered in risk management, namely managers and the characters of different customers.